STUDIES OF THE GENERALIZED SHWARTZMAN REACTION PRODUCED BY DIET : I. PATHOLOGY - McKay, Donald G. (The Rockefeller University Press, 1962)
The generalized Shwartzman reaction can be produced in pregnant rats by dietary means in the absence of injection of exogenous bacterial endotoxin. The experiment consists of a period of exposure to a diet low in tocopherol followed by exposure to a diet containing oxidized lipids during the gestation period. Pregnancy near term is an essential requirement for the development of the generalized Shwartzman reaction in these experiments. Fibrin thrombi were found in the renal glomeruli in 88.5 per cent, in the lungs in 94.2 per cent, in the liver in 11.4 per cent, in the spleen in 11.4 per cent, and in the adrenal in 40 per cent of animals that died spontaneously. There were pathologic alterations in the placenta which consisted of degeneration of the trophoblast, thrombosis of maternal blood channels in the giant cell trophoblast layer and in the labyrinth, congestion of the labyrinth, hemorrhage into the uterine cavity, placental separation, intra-uterine fetal death, decidual and uterine vein thrombosis, and placentitis in 10 per cent of the cases. The mechanism by which the diet is instrumental in causing this reaction remains to be demonstrated.